Varieties within a collective skill formation system: How VET governance in Switzerland is shaped by associations - Regula Bürgi; Philipp Gonon (International Journal for Research in Vocational Education and Training (IJRVET), 2021)
Context: International scholarship and policy tend to depict national structures governing Vocational Education and Training (VET) as uniform and devoid of internal differences. This macro perspective neglects the numerous processes at the meso and micro level that shape the structure and content of VET. This article focusses on professional associations (meso level) in Switzerland to examine the heterogeneity of governance of individual VET programmes that can exist within one country or one collective skill formation system. Approach: Drawing on insights from historical institutionalism and research on corporatism, we argue that these differences are the product of the characteristics, traditional practices and styles of reasoning of the various associations involved in VET governance. Our analysis is based on expert interviews and governance documents in two vocational areas: Electrotechnology and food services. Findings: We identify and decode an array of cooperative practices and show that collective skill formation has a different meaning for different associations and, correspondingly, different occupations. Collaboration with state actors, unions, VET schools and single firms, as well as voting procedures, differ considerably between associations. Furthermore, we find that these different modes of governance are determined by associational characteristics such as size, level of professionalization, location and established cooperative practices, as well as traditional styles of reasonings. Conclusion: The findings indicate that the decisions taken are not always the product of current day training requirements but of historically grown associational characteristics. Thus, path dependencies are to be considered not only at a macro level but also at the meso level. There is a multifaceted variety of governance approaches beneath the classification "collective skill formation system". Associations are key in defining VET content, working life structures and collectivity.
urn:nbn:de:gbv:18-10-4964
Keywords: 330; VET; Vocational Education and Training; Governance; Collective Skill Formation; Historical Institutionalism; Corporatism; Styles of Reasoning in VET